2005
DOI: 10.1177/001440290507100307
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mathematics Professional Standards and Instructional Design Criteria for Problem-Solving in Mathematics

Abstract: This study investigated the extent to which teaching the recommended methods for problem-solving presented in third-grade mathematics textbooks adhered to the National Council of Teachers of Mathematics Standards and instructional design criteria. Results indicated that there were more variations than similarities within and across textbooks in meeting the Standards. In terms of the instructional design criteria, most were satisfied in only two textbooks and few discrepancies were evident across the textbooks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…The Common Core State Standards for Mathematics emphasize a solid understanding of mathematical concepts, a high degree of mathematical procedural skills, and the ability to apply mathematics knowledge to solve real-world problems (Common Core State Standards Initiative 2014). Various types of word problems [i.e., the mathematic questions stated in words (Jitendra et al 2005)] are included in Common Core State Standards for Mathematics (Common Core State Standards Initiative 2014) and students with and without disabilities in the states that have adopted the standards are expected to develop word problem solving ability as required by the standards. Thus, in order for students with ASD to succeed in the general education mathematics curriculum, there is a need to focus on these students' mathematical word problem solving ability and the factors that have the potential to improve this ability.…”
Section: Introductionmentioning
confidence: 99%
“…The Common Core State Standards for Mathematics emphasize a solid understanding of mathematical concepts, a high degree of mathematical procedural skills, and the ability to apply mathematics knowledge to solve real-world problems (Common Core State Standards Initiative 2014). Various types of word problems [i.e., the mathematic questions stated in words (Jitendra et al 2005)] are included in Common Core State Standards for Mathematics (Common Core State Standards Initiative 2014) and students with and without disabilities in the states that have adopted the standards are expected to develop word problem solving ability as required by the standards. Thus, in order for students with ASD to succeed in the general education mathematics curriculum, there is a need to focus on these students' mathematical word problem solving ability and the factors that have the potential to improve this ability.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, traditional mathematics textbooks typically do not provide the kind of instruction recommended by the NCTM. In a study that evaluated five third-grade mathematics textbooks with regard to their adherence to Standards, Jitendra et al (2005) found that the textbooks inadequately addressed them. In particular, opportunities for reasoning and making connections were present in less than half the instances in these textbooks.…”
mentioning
confidence: 99%
“…Providing opportunities to solve a variety of word problems encourages analytic thinking and reasoning. Rather, with traditional instruction, teachers tend to focus on teaching simple memorization of rules, cue words, or specific steps (e.g., Jitendra et al, 2005;Woodward, Monroe, & Baxter, 2001). However, traditional mathematics problem-solving instruction frequently does not provide such experience to students, especially those with disabilities (e.g., Parmar et al, 1996).…”
mentioning
confidence: 99%